Desenvolvimento e estabilidade de bebidas mistas de caju e araçá-boi adicionadas com ômega-3 - Prado, Giovana Matias do (2014)
In spite of the strong appeal that the tropical fmit juice have due to its flavor and the people concern to consume wealthy products, there are many reasons for the production of pure fruit juices and juice products, since they furnish carbohydrates, carotenoids, vitamins phenolic compounds and minerals, important components in the human nutrition and in the control of free radicals. Besides the fruit mixture for beverages, it has been enough studied the addition of components with allegation of functional properties, aiming the preparation of fiuit enriched beverages. The cashew apple is a tropical fmit which Brazilian production is located in the northeast being of great social and economic importance for this region. The cashew apple is source of vitamin C and phenolic compounds with high antioxidant properties. The araça-boi in despite of its excellent sensory properties, is not consumed raw being used in mixtures. Therefore this work have the purpose to develop mixed beverages using araca-boi added with w-3 following the evaluation of its chemical, physicochemical microbiological and sensorial behavior during 120 days of storage besides the bioaccessibility of its phenolic compounds and antioxidants. The mixed beverage was selected in an experiment of response surface, where the more accepted by the global acceptance test was the formulation containing 18.6% of cashew apple and 93.3% of araca-boi. From this formulation, three beverages were prepared: mixed beverage of cashew apple and araca-boi (Fl); mixed beverage of cashew apple and araca-boi added w-3 (F2); and mixed beverage of cashew apple and araca-boi added encapsulated w-3 (F3). Several chemical and physicochemical analysis such as: pH, soluble solids, acidity, total carotenoids, instrumental color and bioactive compounds ascorbic acid, total phenolic compounds and quantification of total antioxidant capacity using the methods ABTS and FRAP. The sensorial evaluation was done through affective tests, evaluating appearance, global acceptance and taste, and the microbiological evaluation analysis through tests of commercial sterility. The experiments were performed in three repetitions and the determinations were done in triplicates. The chemical and physicochemical analysis showed small differences among the formulations and storage time being the methods ABTS and FRAP for antioxidant properties whose which presented greater variations. The parameters pH, soluble solids, acidity total, phenolics, L*, a*, b*, croma and Hue did not present significative interactions among the formulations and the storage time. The pH of the mixed beverages cashew apple and araca-boi showed averages around 3.0. The soluble solids contents remained consistent the fixed values for beverages, around 11 Brix. The ascorbic acid content did not show significative differences among the formulations, arying form 30.32 to 33.31 mg.lOOg of ascorbic acid. The total carotenoids content varied from 187.73 to 242.63 ^ig.lOOg , observing higher values for the formulations containing w- 3. The values for phenolic compounds varied from 74.25 to 88.83 mg AGE. 1 OOg. The sensorial attributes showed a discrete variation during the storage, accept for the mixed beverage of cashew apple and araca-boi added non encapsulated w-3, due to the appearance of strange taste during storage, characteristic to oxidized w-3. Phenolic compounds and antioxidant capacity bioavailability increase during the storage. The production of beverages based on cashew apple and araca-boi is viable through the processing used, and is an alternative to add value for the products from cashew apple and araca-boi.